Use of Biologics to Treat Relapsing and/or Refractory Eosinophilic Granulomatosis With Polyangiitis: Data From a European Collaborative Study. Issue 3 (23rd January 2021) - Canzian, Alice; Venhoff, Nils; Urban, Maria Letizia; Sartorelli, Silvia; Ruppert, Anne‐Marie; Groh, Matthieu; Girszyn, Nicolas; Taillé, Camille; Maurier, François; Cottin, Vincent; de Moreuil, Claire; Germain, Vincent; et al.
Abstract : Objective: To describe the efficacy and safety of biologics for the treatment of eosinophilic granulomatosis with polyangiitis (EGPA). Methods: A retrospective European collaborative study was conducted in patients with EGPA who received treatment with biologics for refractory and/or relapsing disease. Results: Among the 147 patients with EGPA included in the study, 63 received rituximab (RTX), 51 received mepolizumab (MEPO), and 33 received omalizumab (OMA). At the time of inclusion, the median Birmingham Vasculitis Activity Score (BVAS) was 8.5 (interquartile range [IQR] 5–13) in the RTX group, while the median BVAS in the OMA group was 2 (IQR 1–4.5) and the median BVAS in the MEPO group was 2 (IQR 1–5). In patients receiving RTX, the median BVAS declined both at 6 months (median 1, IQR 0–4.5) and at 12 months (median 0, IQR 0–2), and the frequency of remission, partial response, treatment failure, and stopping treatment due to adverse events was 49%, 24%, 24%, and 3%, respectively. For the treatment of glucocorticoid (GC)–dependent asthma, patients who received MEPO had a much better GC‐sparing effect and overall response than did patients who received OMA. The frequency of remission, partial response, treatment failure, and stopping treatment due to adverse events was 15%, 33%, 48%, and 4%, respectively, in the OMA group and 78%, 10%, 8%, and 4%, respectively, in the MEPO group. Remission rates at 12 months were 76% and 82% among patients receiving MEPO at a doses of 100 mg and 300 mg, respectively. Conclusion: These results suggest that RTX could be effective in treating relapses of EGPA vasculitis. MEPO is highly effective with a good safety profile in patients with GC‐dependent asthma. Our data suggest that 100 mg MEPO monthly could be an acceptable dosage for first‐line therapy in selected instances of EGPA, recognizing, however, that this has not been compared to the validated dosage of 300 mg monthly.